Variations from Pattern Bargaining : A Closer Look - Alexander, Kenneth (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1959)
SummaryA union encounters forces which are of sufficient strength to override pressures to negotiate comparable settlements. To gain further insight into the nature of these forces and the union's reaction, the author interviewed union officials of the UAW in Detroit and made a study of 140 collective agreements carried on through the UAW in various industries in the same area.